Implementation of the Principles of Islamic Religious Education curriculum development at Al Hadi Mojolaban Sukoharjo Islamic Junior High School in 2021/2022 - Arifin, Imam; Maksum, Muh. Nur Rochim; Muthoifin, Muthoifin (Jurnal Pendidikan Amartha, 2022)
The purpose of this study is to describe the implementation of curriculum development principles towards the development of the Islamic Religious Education curriculum at Al Hadi Mojolaban Sukoharjo Islamic Junior High School and identify supporting and inhibiting factors in the development of the Islamic religious education curriculum at Al-Hadi Mojolaban Islamic Junior High School. This research is a qualitative descriptive research. The results showed that there are 4 principles in curriculum development, namely religious principles, philosophical principles, social principles and organizational principles. Al-Hadi Islamic Junior High School in developing Islamic religious education has been based on these principles. The form of curriculum development of Islamic education is carried out in intracurricular, co-curricular, extracurricular and school habituation activities.